The Evolving Roles of Macrophages in Organ Transplantation - Junhui Li; Cai Li; Quan Zhuang; Bo Peng; Yi Zhu; Qifa Ye; Yingzi Ming (Journal of Immunology Research)
Organ transplantation is a life-saving strategy for patients with end-stage organ failure. Over the past few decades, organ transplantation has achieved an excellent success in short-term survival but only a marginal improvement in long-term graft outcomes. The pathophysiology of graft loss is multifactorial and remains incompletely defined. However, emerging evidence suggests macrophages as crucial mediators of acute and chronic allograft immunopathology. In this process, macrophage-mediated mobilization of first-line defenses, particularly phagocytosis and the release of acute inflammatory mediators, is important, but macrophages also launch adaptive alloimmune reactions against grafts through antigen processing and presentation, as well as providing costimulation. Additionally, crosstalk with other immune cells and graft endothelial cells causes tissue damage or fibrosis in transplanted organs, contributing to graft loss or tolerance resistance. However, some macrophages function as regulatory cells that are capable of suppressing allogeneic T cells, inhibiting DC maturation, inducing the differentiation of Tregs, and subsequently promoting transplant tolerance. This functional diversity of macrophages in organ transplantation is consistent with their heterogeneity. Although our knowledge of the detrimental or beneficial effects of macrophages on transplants has exponentially increased, the exact mechanisms controlling macrophage functions are not yet completely understood. Here, we review recent advances in our understanding of the multifaceted nature of macrophages, focusing on their evolving roles in organ transplantation and the mechanisms involved in their activation and function in allograft transplantation. We also discuss potential therapeutic options and opportunities to target macrophage to improve the outcomes of transplant recipients.